PROSES MEDIASI DALAM PENYELESAIAN PERCERAIAN DI PENGADILAN AGAMA PEKANBARU - Risa Pertiwi; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research was conducted at the Pekanbaru Religious Court office with the aim of finding out the involvement of the parties in the mediation process and the role of the Pekanbaru Religious Court Mediator in reconciling a married couple who wanted to divorce. This research uses descriptive qualitative research method. The subjects in this study amounted to 5 people as key informants and 3 pairs of husband and wife as informants. In collecting the data, researchers used observation techniques, in-depth interviews and documentation. The results of the descriptive analysis indicate that every case in the Religious Courts must follow the mediation process first before the case is decided by the Panel of Judges with the appointed Mediator. The parties referred to here are Judges, Bailiffs and Mediators who are involved from the pre-mediation stage until the mediation takes place. However, when mediation takes place there are only mediators and married couples who are in the mediation room, because mediation is closed. The researcher's observation result shows that the role and interaction established by the Mediator as a neutral party from both parties to the litigation is to make the mediation atmosphere as comfortable as possible and try to be a trusted person so that the husband and wife want to reveal all the problems they face and give advice and solve the problems they face. The effort to build one's trust is the main thing that must be done by a Mediator, because that way the couple who want to divorce earlier can devote their whole heart to the Mediator and the Mediator can more easily identify their problems so they can provide a good way out for them.Keywords: Mediation Process, Divorce Settlement.